2023
DOI: 10.1177/21582440231180672
|View full text |Cite
|
Sign up to set email alerts
|

Audit Quality, Institutional Environments, and Earnings Management: An Empirical Analysis of New Listings

Chi Duong Thi

Abstract: The purpose of this article is to investigate the relationship between audit quality, the role of institutional environments at the provincial level, and earnings management around listing events by using data from 189 newly-listed companies on the Hochiminh Stock Exchange. Audit quality was proxied by Big4, auditor tenure, and auditor industry specialization, while earnings management was quantified as current discretionary accruals. The findings indicated that there was no role for Big 4, auditor tenure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 131 publications
2
5
0
Order By: Relevance
“…The coefficient b 2 of the control variable A_AC i,t , proxying the absolute value of the discretionary accruals, shows a positive sign, as expected, though it is not significant. This finding, consistent with previous literature (Abid et al, 2018;Bradshaw et al, 2001;Butler et al, 2004;Duong Thi, 2023), indicates that accrual-based earnings management initiatives do not drive the probability of receiving a modified audit opinion. The coefficient b 3 of the control variable B4 i,t , a dummy variable proxying the engagement of a Big-N auditor, shows a negative but not significant sign, contrary to our expectations.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The coefficient b 2 of the control variable A_AC i,t , proxying the absolute value of the discretionary accruals, shows a positive sign, as expected, though it is not significant. This finding, consistent with previous literature (Abid et al, 2018;Bradshaw et al, 2001;Butler et al, 2004;Duong Thi, 2023), indicates that accrual-based earnings management initiatives do not drive the probability of receiving a modified audit opinion. The coefficient b 3 of the control variable B4 i,t , a dummy variable proxying the engagement of a Big-N auditor, shows a negative but not significant sign, contrary to our expectations.…”
Section: Resultssupporting
confidence: 91%
“…, 2001; Butler et al. , 2004; Duong Thi, 2023), indicates that accrual-based earnings management initiatives do not drive the probability of receiving a modified audit opinion. The coefficient β 3 of the control variable B4 i,t , a dummy variable proxying the engagement of a Big-N auditor, shows a negative but not significant sign, contrary to our expectations.…”
Section: Resultsmentioning
confidence: 99%
“…At a global level, the results confirm that the longer the auditor tenure, the higher the quality of the results. Therefore, these results are in line with those authors who argue against mandatory auditor rotation, as greater experience at the company facilitates the detection of accounting practices aimed at manipulating financial results (Duong Thi, 2023;Hsu & Liao, 2023;Kuang et al, 2020;Le & Moore, 2023;Lin & Yen, 2022;Nekhili et al, 2022). Therefore, these results contradict those that, based on the theory of influence, advocate the establishment of a mandato-ry auditor rotation (Bamahros & Wan Hussin, 2015;Firth et al, 2012;Tran et al, 2023;Zgarni et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…In fact, this research pro-vides some indication of superior auditing quality for such firms. Likewise, researchers such as Nekhili et al (2022), Duong Thi (2023, Hsu and Liao (2023), and Le and Moore (2023) found that the longer the auditor tenure, the lower the EM. This therefore implies that auditor rotation does not reduce EM.…”
Section: Auditor Tenure and Emmentioning
confidence: 97%
See 1 more Smart Citation